{110} crystal face exposed rutile type titanium dioxide nano material as well as preparation method and application thereof
The gold -red stone titanium dioxide nanomaterials exposed by the crystal surface of the crystal surface are prepared through the water heat synthesis method, which solves the problem of low magnesium storage capacity and poor performance performance of magnesium -based ion batteries, and realizes high -efficiency magnesium ion storage and battery performance improvement.
Patent Information
- Application Number
- CN202411465113.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
Magnesium-based ion batteries have two positive charges, resulting in relatively slow ion migration, low magnesium storage capacity and poor rate performance.
Through a hydrothermal synthesis method, using hydrochloric acid and sodium fluoride as structure control agents, rutile titanium dioxide nanomaterials with exposed {110} crystal planes were prepared. The preparation process of this material is simple and efficient, and the obtained nanomaterial has high purity and smooth surface.
Improve the magnesium storage capacity and magnification performance of magnesium ion batteries. The preparation methods are simple and repetitive, and are suitable for large -scale industrialized production.
Smart Images

Figure CN119349628A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of battery material technology, catalysis and sensors, and in particular to a rutile titanium dioxide nanomaterial with exposed {110} crystal planes, a preparation method and an application thereof. Background Art
[0002] Rechargeable magnesium-ion batteries (MIBs) have better safety and reliability than lithium batteries, are cheaper, and have a larger volumetric capacity. In addition, my country has abundant magnesium resources, making magnesium-ion batteries a candidate battery for the post-lithium-ion battery era. Despite the many potential advantages of magnesium-ion batteries, there are still many problems that hinder their practical application. For example, each magnesium ion carries two units of positive charge, which has a greater electrostatic effect than lithium ions, resulting in relatively slow ion migration. Therefore, the development of positive electrode materials with efficient magnesium storage performance is crucial to the development of magnesium-based ion batteries.
[0003] Titanium dioxide has a highly reactive surface and has attracted extensive research interest due to its high photocatalytic activity and electrochemical performance. The chemical properties of different crystal faces (such as anatase {001} and {100} faces). However, compared with the great achievements made on anatase crystals with high reactive faces, there are fewer studies on other high-energy face phases of titanium dioxide, such as rutile. Studies have shown that rutile {110} crystal faces have the highest surface energy and high reactivity. Therefore, it is key to controllably prepare rutile titanium dioxide nanoparticles with a high proportion of {110} crystal faces. Based on the above considerations, a simple synthesis technique, namely hydrothermal synthesis, can be used to synthesize rutile titanium dioxide with smooth crystal faces and large exposed faces, and apply it as a positive electrode material for magnesium-based ion batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a rutile titanium dioxide nanomaterial with exposed {110} crystal planes, a preparation method and an application thereof. The preparation process is simple and efficient, and the obtained rutile titanium dioxide has high purity and a smooth surface, thereby solving the problems of low magnesium storage capacity and poor rate performance of existing magnesium-based batteries.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a method for preparing a rutile titanium dioxide nanomaterial with an exposed {110} crystal face, the method comprising: adding a titanium source to a hydrochloric acid solution and mixing and stirring to obtain a mixed solution; adding sodium fluoride to the mixed solution to obtain a reaction precursor; transferring the reaction precursor to a reactor for a hydrothermal reaction; after the reaction is completed, cooling, separating, washing, and drying to obtain a rutile titanium dioxide nanomaterial with an exposed {110} crystal face.
[0006] Further, 0.015 M of titanium source and 0.015 M of sodium fluoride were added to every 3.5 M of hydrochloric acid solution; The titanium source includes titanium tetrachloride, tetrabutyl titanate or tetraisopropyl titanate.
[0007] Furthermore, the temperature of the hydrothermal reaction is 100-200° C., and the hydrothermal reaction time is 16-24 hours.
[0008] Furthermore, the obtained rutile titanium dioxide nanomaterial with exposed {110} crystal planes is a nanoparticle with smooth tetragonal prism crystal faces.
[0009] Furthermore, the separation method is centrifugation or filtration; the washing solvent is at least one of deionized water, anhydrous ethanol and acetone, and the product is washed with the washing solvent until the pH of the product is neutral; the drying method is at least one of natural drying, forced air drying, freeze drying and vacuum drying.
[0010] In a second aspect, the present invention provides a rutile titanium dioxide nanomaterial with exposed {110} crystal plane, which is prepared by the above-mentioned method for preparing a rutile titanium dioxide nanomaterial with exposed {110} crystal plane.
[0011] In a third aspect, the present invention provides a use of a rutile titanium dioxide nanomaterial with exposed {110} crystal planes, prepared by the method for preparing a rutile titanium dioxide nanomaterial with exposed {110} crystal planes as described above, in a positive electrode material for a magnesium-based battery.
[0012] Beneficial effects of the present invention: The present invention uses hydrochloric acid and sodium fluoride as structure control agents of titanium dioxide nanomaterials, and prepares rutile titanium dioxide nanomaterials with exposed {110} crystal faces through a hydrothermal synthesis method. The obtained rutile titanium dioxide nanomaterials have high purity and smooth surface energy, and can be used as positive electrode materials for magnesium ion batteries and magnesium-lithium hybrid batteries. The preparation method is simple, reproducible, easy to operate, and is expected to be applied to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a flow chart of a method for preparing a rutile titanium dioxide nanomaterial with exposed {110} crystal planes provided in an embodiment of the present invention.
[0014] Figure 2 This is a SEM image of the rutile titanium dioxide nanomaterial with exposed {110} crystal planes prepared in Example 1 of the present invention.
[0015] Figure 3 This is the SEM image of the positive electrode material prepared in comparative example.
[0016] Figure 4This is the XRD diagram of the rutile titanium dioxide nanomaterial with exposed {110} crystal plane prepared in Example 1 of the present invention.
[0017] Figure 5 The figure is a charge and discharge curve diagram of a rechargeable magnesium battery assembled from rutile titanium dioxide nanomaterials with exposed {110} crystal planes prepared in Example 1 of the present invention in an APC+LiCl mixed electrolyte.
[0018] Figure 6 The figure is the charge and discharge curve of the rutile titanium dioxide nanomaterial with exposed {110} crystal plane prepared in Example 1 of the present invention after being assembled into a rechargeable magnesium battery in APC electrolyte. DETAILED DESCRIPTION
[0019] The following will describe the embodiments of the present invention with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention, not for limiting the scope of protection of the present invention.
[0020] In one embodiment, see Figure 1 As shown, the present invention provides a method for preparing a rutile titanium dioxide nanomaterial with an exposed {110} crystal face, the method comprising: adding a titanium source to a hydrochloric acid solution and mixing and stirring to obtain a mixed solution; adding sodium fluoride to the mixed solution to obtain a reaction precursor; transferring the reaction precursor to a reactor for a hydrothermal reaction; after the reaction is completed, cooling, separating, washing, and drying to obtain a rutile titanium dioxide nanomaterial with an exposed {110} crystal face.
[0021] The present invention successfully prepared anatase titanium dioxide nanosheets with {001} crystal plane exposed by combining hydrofluoric acid solution with hydrothermal synthesis reaction. By exposing the crystal plane with the highest surface energy of titanium dioxide, the larger specific surface area gives the material more magnesium ion adsorption sites and broad ion diffusion channels, thereby achieving the purpose of reducing the diffusion energy barrier of magnesium ions in the structure, promoting the storage of magnesium ions in the structure, and improving the battery capacity. The obtained anatase titanium dioxide nanosheets with {001} crystal plane exposed have high specific capacity, low diffusion energy barrier, and high stability. At 500 mAg -1 After 1000 cycles under the current line, the specific capacity can still be maintained above 75%.
[0022] In a preferred embodiment, 0.015 M titanium source and 0.015 M sodium fluoride are added to every 3.5 M hydrochloric acid solution; The titanium source includes titanium tetrachloride, tetrabutyl titanate or tetraisopropyl titanate.
[0023] Amount and concentration of hydrochloric acid solution: 40~60mL of hydrochloric acid solution with a concentration of 2.5~4.0M is selected as the reaction medium. Hydrochloric acid in this concentration range not only provides a suitable acidic environment for the titanium source, but also facilitates the dissolution of sodium fluoride and the subsequent hydrothermal reaction.
[0024] Amount and type of titanium source: In this embodiment, it is clearly pointed out that the titanium source includes titanium tetrachloride, tetrabutyl titanate or tetraisopropyl titanate, and a specific dosage range is given, that is, 0.015M of titanium source is added to every 3.5M hydrochloric acid solution. This dosage range not only ensures the effective concentration of the titanium source in the reaction system, but also avoids the side reactions that may be caused by excessive use.
[0025] Dosage of sodium fluoride: The amount of sodium fluoride added is set as follows: 0.015M titanium source and 0.015M sodium fluoride are added to every 3.5M hydrochloric acid solution. Fluoride ions play a key role in the reaction. They form complexes with titanium ions, thereby affecting the crystal growth direction and crystal face exposure of rutile titanium dioxide. An appropriate amount of sodium fluoride can effectively promote the exposure of the {110} crystal face and improve the performance of the product.
[0026] It should be noted that although titanium tetrachloride is specifically mentioned as a titanium source in the specific example, it does not mean that other titanium sources (such as tetrabutyl titanate and tetraisopropyl titanate) cannot be used in the reaction. In fact, different titanium sources may have different effects on the reaction process and product properties, so they can be selected and optimized according to specific needs in practical applications.
[0027] In a preferred embodiment, the temperature of the hydrothermal reaction is 100-200° C., and the hydrothermal reaction time is 16-24 hours.
[0028] The temperature of the hydrothermal reaction is set to 100~200℃. Within this temperature range, the molecular movement in the reaction system is accelerated, which is conducive to the hydrolysis and polycondensation of the titanium source, as well as the coordination of fluoride ions and titanium ions. At the same time, high temperature also helps to accelerate the crystal growth process, but too high a temperature may cause changes in the crystal structure or the occurrence of side reactions, so it is necessary to select an appropriate temperature within this range for the experiment.
[0029] On the other hand, the hydrothermal reaction time is set to 16~24h. During this period of time, the reactants can fully react and transform into the target product. A sufficiently long reaction time can ensure complete crystal growth and promote the exposure of the {110} crystal plane. However, too long a reaction time may also cause excessive crystal growth or agglomeration, affecting the performance of the product. Therefore, it is also very important to choose an appropriate reaction time within this time range.
[0030] In summary, by controlling the temperature of the hydrothermal reaction between 100 and 200 °C and the reaction time between 16 and 24 h, rutile titanium dioxide nanomaterials with exposed {110} crystal planes and excellent performance can be effectively prepared.
[0031] In a preferred embodiment, the obtained rutile titanium dioxide nanomaterial with exposed {110} crystal planes is a nanoparticle with smooth tetragonal prism crystal faces.
[0032] The formation of tetragonal prism faces is achieved by precisely controlling the hydrothermal reaction conditions (such as temperature, time, reactant concentration, etc.). These conditions act together on the reaction system to promote the preferential growth of rutile titanium dioxide crystals in the {110} crystal plane direction. As the reaction proceeds, the crystals gradually grow and form tetragonal prism-shaped nanoparticles with smooth surfaces.
[0033] In a preferred embodiment, the separation method is centrifugation or filtration; the washing solvent is at least one of deionized water, anhydrous ethanol and acetone, and the product is washed with the washing solvent until the pH of the product is neutral; the drying method is at least one of natural drying, forced air drying, freeze drying and vacuum drying.
[0034] First, in the separation step, two methods, centrifugation or filtration, are used. Centrifugation is a method that uses centrifugal force to separate the reaction product from the solution. It is suitable for processing a large amount of products and can complete the separation process quickly. Filtration is a method that uses negative pressure to form a filter cake on the filter paper and then separate it from the solution. It is suitable for processing products with high viscosity or fine particles. Both methods can effectively separate titanium dioxide nanosheets from the reaction solution, providing convenience for subsequent processing.
[0035] Secondly, in the washing step, at least one of deionized water, anhydrous ethanol and acetone is selected as the washing solvent. These solvents have good solubility and volatility, and can effectively remove residues and impurities on the surface of the product. By washing multiple times until the pH value of the product is neutral, the purity and stability of the product can be ensured. During the washing process, it is necessary to pay attention to controlling the number of washings and the washing time to avoid unnecessary loss or damage to the product.
[0036] Finally, in the drying step, a variety of drying methods are provided for selection, including at least one of forced air drying, natural drying, freeze drying and vacuum drying. Forced air drying is a method of using hot air to quickly evaporate the water or solvent in the product, which is suitable for processing a large amount of products and requiring drying time. Natural drying is a method of placing the product in a well-ventilated environment for natural air drying, which is suitable for situations where there are no strict requirements for drying time and the output is not large. Freeze drying is a method of removing moisture from the product by sublimation under reduced pressure after freezing the product at low temperature, which is suitable for processing products that are volatile or heat-sensitive. Vacuum drying is a method of heating and drying the product under vacuum conditions, which can accelerate the drying process and reduce the contact time of the product with oxygen, thereby protecting the performance of the product.
[0037] In one embodiment, the present invention further provides a rutile titanium dioxide nanomaterial with exposed {110} crystal plane, which is prepared by the preparation method of the rutile titanium dioxide nanomaterial with exposed {110} crystal plane as described above.
[0038] In one embodiment, the present invention further provides a use of a rutile titanium dioxide nanomaterial with exposed {110} crystal planes obtained by the above-mentioned method for preparing a rutile titanium dioxide nanomaterial with exposed {110} crystal planes in a positive electrode material for a magnesium-based battery.
[0039] Furthermore, the present invention also provides a method for preparing a positive electrode sheet, comprising the following steps: 1) The prepared rutile titanium dioxide nanomaterial with exposed {110} crystal plane is used as the positive electrode active material, and the positive electrode active material is ground and uniformly mixed with a binder and a conductive agent in a mass ratio of 7:2:1 to obtain a mixed material. The mixed material is then added to NMP (N-methylpyrrolidone) and stirred for 8-12 hours to obtain a positive electrode material slurry.
[0040] 2) Apply the positive electrode material slurry on carbon paper or molybdenum foil, put it in a vacuum oven, and dry it at 80-100°C for 10-12 hours to obtain a positive electrode sheet. Finally, cut the positive electrode sheet into a disc with a diameter of 10 mm and put it in a glove box for standby use.
[0041] Magnesium-based battery assembly, the positive electrode plate is made of rutile titanium dioxide nanomaterial with exposed {110} crystal plane obtained by the preparation method of the present invention as the positive electrode active material, and the negative electrode uses magnesium foil with a purity of 99.9% or 99.99%. The magnesium foil needs to be surface polished before use. Use sandpaper with a mesh size of 1200 or above to polish it until the surface is smooth and scratch-free. Then put it in anhydrous alcohol for ultrasonic cleaning, and finally put it in a vacuum oven to dry to obtain the negative electrode.
[0042] The electrolyte is reasonably selected according to the type of assembled battery. For example, when the assembled battery is a magnesium-ion battery, the electrolyte is a commercial APC electrolyte. When the assembled battery is a magnesium-lithium hybrid battery, the electrolyte is 0.4 M LiCl + 0.4 M APC mixed electrolyte. The preparation method is as follows: weigh 0.2~1g lithium chloride (LiCl) and add it to 10~20 ml commercial APC electrolyte, stir for more than 10h to obtain a mixed electrolyte.
[0043] It should be noted that the battery consists of a positive electrode, a negative electrode, and an electrolyte as well as a separator and a current collector. The separator is a glass fiber separator known in the art, and the current collector is a non-corrosive current collector such as carbon paper. The battery assembly and electrolyte configuration are carried out in a glove box filled with argon gas, with the water content and oxygen content maintained below 0.01ppm.
[0044] The following is an explanation with reference to specific examples.
[0045] Embodiment 1, a method for preparing anatase titanium dioxide nanosheet with exposed {001} crystal plane, the method comprising the following steps: S1, adding titanium tetrachloride into a hydrochloric acid solution and mixing with stirring to obtain a mixed solution.
[0046] S2, adding sodium fluoride to the mixed solution to obtain a reaction precursor, wherein 0.015 M of titanium source and 0.015 M of sodium fluoride are added to every 3.5 M of hydrochloric acid solution.
[0047] S3, transferring the reaction precursor to a reactor for hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 220° C. and the hydrothermal reaction time is 12 h. After the reaction is completed, cooling, separation, washing, and drying are performed to obtain a rutile titanium dioxide nanomaterial with exposed {110} crystal planes.
[0048] Comparative Example: A method for preparing rutile titanium dioxide nanosheets with exposed {110} crystal planes is provided, and the main steps are the same as those in the above embodiment, except that the added titanium source and the concentration of hydrochloric acid are different. Specifically, 5 mL of tetrabutyl titanate is added to 60 mL of a hydrochloric acid solution with a concentration of 36-38%, and the mixture is mixed and stirred to obtain a mixed solution. 0.04 g of sodium fluoride is added to the mixed solution to obtain a reaction precursor. The reaction precursor is transferred to a reactor for a hydrothermal reaction; the temperature of the hydrothermal reaction is 220 °C, and the hydrothermal reaction time is 12 h. After the reaction is completed, the comparative product is obtained by cooling, separation, washing, and drying. Among them, the separation method is centrifugation, the speed is 10000-13000 rpm, and the number of centrifugation is 3-6 times. The washing solvent is deionized water, and the product is washed to neutrality by the washing solvent; the drying method is natural drying, freeze drying or vacuum drying (specific drying temperature and drying time can also be provided according to actual needs).
[0049] The product obtained in Example 1 was subjected to SEM analysis, and the results are shown in Figure 2 , indicating that the obtained product is a uniformly distributed, smooth crystalline particle in the shape of a square prism.
[0050] The product obtained in the comparative example was subjected to SEM analysis, and the results are shown in Figure 3 The product obtained in the comparative example is a relatively large block-shaped polyhedral crystal with uneven surface distribution.
[0051] The product obtained in Example 1 was subjected to XRD analysis, and the results are shown in Figure 4 , with an obvious main peak, the product is pure crystalline particles with exposed {110} faces.
[0052] In order to verify the performance of the product obtained in Example 1, the rutile titanium dioxide nanomaterial with exposed {110} crystal plane obtained in Example 1 was used as the positive electrode active material to prepare a positive electrode sheet, and then a magnesium-based battery was assembled. The magnesium-based battery assembly specifically includes the following steps: 1) The rutile titanium dioxide nanomaterial with exposed {110} crystal plane prepared in Example 1 was used as the positive electrode active material. The positive electrode active material was ground and uniformly mixed with a binder and a conductive agent in a mass ratio of 7:2:1 to obtain a mixed material. The mixed material was then added to NMP (N-methylpyrrolidone) and stirred for 12 h to obtain a positive electrode material slurry.
[0053] 2) Apply the positive electrode material slurry on carbon paper or molybdenum foil, put it in a vacuum oven, and dry it at 80°C for 12 hours to obtain a positive electrode sheet. Finally, cut the positive electrode sheet into a disc with a diameter of 10 mm and put it in a glove box for standby use.
[0054] 3) Prepare electrolyte. There are two types of electrolytes: magnesium ion electrolyte and magnesium-lithium dual salt mixed electrolyte. The magnesium ion electrolyte is commercial APC electrolyte. The magnesium-lithium mixed electrolyte is 0.4 M LiCl + 0.4 M APC electrolyte. The preparation method is as follows: weigh 0.2 g of lithium chloride (LiCl) and add it to 10 mL of commercial APC electrolyte. Stir for more than 10 hours to obtain a mixed electrolyte.
[0055] 4) Prepare the negative electrode. Use 1200-grit sandpaper to polish a 0.1mm thick and 11mm diameter magnesium foil disc. After polishing until there are no scratches and it is bright, put it into anhydrous ethanol for ultrasonic cleaning. Then put it into a vacuum oven and dry it at 60°C for 12 hours. Finally, transfer it to the glove box for use.
[0056] 5) Using a battery shell, the separator and the positive electrode sheet, the negative electrode sheet and the electrolyte prepared by the above method are conventionally assembled to obtain a magnesium-based battery.
[0057] The electrochemical performance of the obtained magnesium-based battery was tested, and the results are shown in Figure 5 and Figure 6 .
[0058] Depend on Figure 5 It can be seen that the positive electrode material prepared in Example 1 can have a discharge specific capacity of up to 120 mAh / g in a double salt electrolyte, and the current density used in the test is 50 mA / g.
[0059] Depend on Figure 6 It can be seen that the positive electrode material prepared in Example 1 has a specific capacity of 65 mAh / g in a pure magnesium electrolyte at a low current.
Claims
1. A method for preparing a rutile titanium dioxide nanomaterial with exposed {110} crystal planes, characterized in that: The method comprises: adding a titanium source into a hydrochloric acid solution and mixing and stirring to obtain a mixed solution; adding sodium fluoride to the mixed solution to obtain a reaction precursor; The reaction precursor is transferred to a reactor for a hydrothermal reaction; after the reaction is completed, the rutile titanium dioxide nanomaterial with the {110} crystal plane exposed is obtained through cooling, separation, washing and drying.
2. The method for preparing a rutile titanium dioxide nanomaterial with exposed {110} crystal plane according to claim 1, characterized in that: Add 0.015 M titanium source and 0.015 M sodium fluoride to every 3.5 M hydrochloric acid solution; The titanium source includes titanium tetrachloride, tetrabutyl titanate or tetraisopropyl titanate.
3. The method for preparing a rutile titanium dioxide nanomaterial with exposed {110} crystal plane according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 100-200° C., and the hydrothermal reaction time is 16-24 hours.
4. The method for preparing a rutile titanium dioxide nanomaterial with exposed {110} crystal plane according to claim 1, characterized in that: The obtained rutile titanium dioxide nanomaterial with exposed {110} crystal planes is a nanoparticle with smooth tetragonal prism crystal faces.
5. The method for preparing anatase-type titanium dioxide nanomaterial with exposed {001} crystal plane according to claim 1, characterized in that: The separation method is centrifugation or filtration; The washing solvent is at least one of deionized water, anhydrous ethanol and acetone, and the product is washed with the washing solvent until the pH of the product is neutral; The drying method is at least one of natural drying, forced air drying, freeze drying and vacuum drying.
6. A rutile titanium dioxide nanomaterial with exposed {110} crystal planes, characterized in that: The nanomaterial is prepared by the method for preparing a rutile titanium dioxide nanomaterial with exposed {110} crystal plane as described in any one of claims 1 to 5.
7. Use of a rutile titanium dioxide nanomaterial with exposed {110} crystal planes obtained by the method for preparing a rutile titanium dioxide nanomaterial with exposed {110} crystal planes as claimed in any one of claims 1 to 5 in a positive electrode material for a magnesium-based battery.
Citation Information
Patent Citations
Large-area growing method for single crystal titanium dioxide nano rod and application of nano rod
CN102146586A
Preparation method for TiO2 with photocatalytic activity under visible light
CN102658104A
Method for modulating titanium dioxide crystalline phases by using fluoride ions
CN103274461A
Rechargeable magnesium battery
CN104538669A
Method for controllably synthesizing different crystal forms of waxberry-shaped titanium dioxide nanometer materials
CN109110806A